Pós-humanismo enquanto uma versão secularizada da ensomatose gnóstica: corpo e modernidade técnica abordados através da sociologia do conhecimento - Prazeres, Alexandre de Jesus dos (2019)
This research carried out in the field of Sociology, more specifically the Sociology of Knowledge and Technique, aims to investigate the presence in the secularized consciousness of modern society of a religious unconsciousness. This religious unconsciousness manifests itself through theological conceptions laicized in modern phenomena which, in themselves, are not explicitly religious, bring the religious notions implicitly and in a way that those involved in phenomena do not often refuse to admit the presence of these notions in his way of thinking. To exemplify the sustained thesis, the research chose trans or post-humanism as a modern phenomenon (which fed its imaginary of advances from science and modern technique) with analogous notions the religious conceptions of a Gnostic eschatology. Thus, the text of the research was elaborated in a way that in the first chapter expounded from where emerges the post-humanist thought, presented a more general picture, exposing Technical Modernity as existential basis of this knowledge. On the other hand, in the second chapter, the concepts of secularization and legitimacy applied to Modernity were approached from a philosophical point of view. In the third chapter, the concept of secularization was retaken as a sociology problem, since chapter two dealt with philosophical questions about this concept. Consequently, in the fourth chapter, the analogical relationship between posthumanism and gnosticism will be explored. This chapter, by exposing the elements that characterize Gnostic thought and its important influence in the formation of ideas in the West, brings the reader closer to the theological concepts that have been secularized in Modernity, at the same time that allows a closer approximation of the example, in this research, post-human thought. The latter is described as analogous to gnosis and full of unfoldings that describe a Gnostic eschatological logic.